Microbiological Characteristics of Trachanas, a Traditional Fermented Dairy Product from Cyprus - Bozoudi, Despina; Agathokleous, Maria; Anastasiou, Iacovos; Papademas, Photis; Tsaltas, Dimitrios (My University, 2017)
The purpose of this study was to characterize the autochthonous microbiota of Cypriot Trachanas, a traditional fermented ewes’ milk product. For this reason, 12 samples of raw and fermented milk as well as natural starter culture were collected in order to count, isolate, and identify the main species present during Trachanas fermentation. In total, 198 colonies were retrieved and 163 were identified by sequencing analysis at species level. Lactic acid bacteria (LAB) were the predominant group, followed by yeasts. Lactococcus, Lactobacillus, and Enterococcus were frequently isolated from raw milk, and Lactobacillus casei/paracasei predominated in the starter culture. Lactococcus lactis was isolated in high frequency (27.9% of the isolates) at the beginning, while Lactobacillus spp. (20%) and Saccharomyces unisporus (17.9%) were isolated at the end of fermentation. After assessing their technological potential, selected strains could be used as starters to ferment milk for artisanal Trachanas production.
Keywords: Cheese; Cheeses; Control cheese